Pearson and Pedagogy: Countering Co-Dependency - Fielder, John (The Australian Journal of Indigenous Education, 2008)
Abstract Noel Pearson and Marcia Langton have both used the terms “co-dependency” and “rescuing” as part of their challenge to the rights-based focus informing Indigenous policies in Australia since the 1960s. Their premise is that the liberal/Left welfare-based agenda, for decades, has largely overlooked Indigenous responsibility. At the same time, they recognise that policy frameworks strongly influence agency and individual responsibility. I examine the implications of this argument within the tertiary education environment, using systems theory to foreground the complexity of individual change within well-established social patterns. This paper reflects on how my thinking and pedagogy have generally been based on a “moral vanity” that, at times, has sanctioned shallow and passive learning experiences that have failed to challenge student achievement.